LOCAL BUDGETS IN THE CONDITIONS OF FINANCIAL DECENTRALIZATION - Rubai О.; Syniavska Л.; Kolodii А. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The article examines the role of local budgets in the conditions of financial decentralization, as one of the key reform processes in Ukraine to ensure effective development of local communities. The purpose of the article is to study the formation of local budgets in conditions of decentralization to strengthen the financial capacity of local self-government bodies. The systematization of literary sources on the study of the role of local budgets in the conditions of financial decentralization made it possible to find out in the work that it is the main source of financing local needs in the fields of education, health care, culture, social protection, improvement and other areas since the creation of the UTC allowed to unite small communities into larger ones with more population and resources. This enables local self-government bodies to better perform their functions and effectively finance the development of their territories. An analysis of the revenue part of the budget of the administrative-territorial unit was carried out using the example of the budget of the Drohobych city territorial community, which showed that financial decentralization led to a significant increase in local budget revenues. Studies have shown that the largest specific share in the structure of the revenue part of local budgets is provided by tax revenues, namely a personal income tax, a single tax, and a tax on property other than land. Based on this, it is expedient for the heads of united communities to focus on the development of private entrepreneurship, legalization of labor relations, wage increases in business entities, and other measures aimed at increasing income from the administration of personal income tax. Based on the conducted research, it is found that decentralization opens up new opportunities for the development of local communities, and the effective filling and use of local budgets is a key factor in successful decentralization.